2014
DOI: 10.1155/2014/576249
|View full text |Cite
|
Sign up to set email alerts
|

Children Living near a Sanitary Landfill Have Increased Breath Methane andMethanobrevibacter smithiiin Their Intestinal Microbiota

Abstract: This study evaluated the breath CH4 excretion and concentration of M. smithii in intestinal microbiota of schoolchildren from 2 slums. One hundred and eleven children from a slum near a sanitary landfill, 35 children of a slum located away from the sanitary landfill, and 32 children from a high socioeconomic level school were included in the study. Real-time PCR was performed to quantify the M. smithii nifH gene and it was present in the microbiota of all the participating children, with higher (P < 0.05) conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…Environmental effects may also play a role, as children living near landfills, which had higher atmospheric methane than areas away from landfills, had a higher breath methane output and higher Mbr. smithii cell density than control children, regardless of their socioeconomic level [34]. Previous to that study, it was shown that the bacterial and fungal counts dispersed from landfills into air were up to 20 times higher than microbial counts from other areas [98].…”
Section: Mitigation Strategiesmentioning
confidence: 84%
See 1 more Smart Citation
“…Environmental effects may also play a role, as children living near landfills, which had higher atmospheric methane than areas away from landfills, had a higher breath methane output and higher Mbr. smithii cell density than control children, regardless of their socioeconomic level [34]. Previous to that study, it was shown that the bacterial and fungal counts dispersed from landfills into air were up to 20 times higher than microbial counts from other areas [98].…”
Section: Mitigation Strategiesmentioning
confidence: 84%
“…This allows methane production to be indirectly and noninvasively measured, since breath methane concentration is correlated with methanogen cell density in the intestines [1]. An undetectable concentration of breath methane does not equate to the absence of archaea, and therefore false-negative interpretations of breath gas analysis may result when breath methane is at undetectably low levels [33,34]. Reported estimations suggest that between 30 and 62% of healthy humans produce detectable methane [31,35].…”
Section: Intestinal Methane and The Effect On The Hostmentioning
confidence: 99%
“…Although diet has been the primary research focus concerning intestinal microbial diversity, we take this opportunity to highlight that other external environmental factors also seem to play a role in how intestinal microbial communities take their shape [ 66 – 70 ]. In other words, it is entirely possible that natural environments can impact upon all human-associated microbial communities, which in turn could influence nerve cell communication.…”
Section: Microbes Phytoncides Ions—air To Brain?mentioning
confidence: 99%
“…Antibiotic exposure is often higher in disadvantaged populations [260,261,262]. The microbes carried by mammals are also a product of the ecosystems in which they reside [263,264,265,266]; given that the Earth is home to upward of 1 trillion microbial species [267], human contact with many of these microbes in natural environments (the ecosystem in which we once spent the majority of our time) may have evolutionary-rooted, health-protective properties.…”
Section: Hygiene Hypothesis Dysbiotic Driftmentioning
confidence: 99%